PENGARUH PENGGUNAAN TEPUNG DAUN BELIMBING MANIS (Averrhoa carambola L.) SEBAGAI SUBSTITUSI PAKAN KELINCI TERHADAP PERFORMA KELINCI HYLA HYCOLE - Aldo Ulva Rinanto; Nita Opi Ari Kustanti; Anang Widigdyo (Universitas Islam Balitar, 2018)
Research data collection was carried out from 12 June to 24 July 2019 at Ridho Rabbitry farm, Nglegok sub-district, Blitar district, East Java. This study aims to determine the effect of the use of sweet starfruit leaf flour (Averrhoa carambola L.) as a substitute for peanut skin on body weight gain and feed conversion of rabbit hyla hycole. The research material used 24 hyla hycole rabbits aged 12 weeks were used in this study with rabbit body weights 1900-2550 g/head, which were divided into four treatments and three replications. Experimental design with Randomized Block Design (RBD). The results showed that the average treatment, namely P0, P1, P2 and P3, respectively for feed consumption 127.33; 128.67; 124.67 and 128.33 (grams/head/day), weight gain 69.17; 80.00; 69.17 and 118.33 (grams/head/week), feed conversion 13.47; 11.30; 12.01 and 7.60.The results of this studies shows that the use of sweet starfruit leaf flour (Averrhoa carambola L.) as a substitution of peanut shells to a level of 15% has no significant effect (P> 0.05), but can affect the performance of hyla hycole rabbits including consumption feed, weight gain and feed conversion and do not have a negative impact on rabbits so that sweet starfruit leaf flour (Averrhoa carambola L) can be used as a substitute for peanut shells.